Adaptive vibration reshaping based milling chatter suppression. (June 2019) - Wang, Chenxi; Zhang, Xingwu; Liu, Jinxin; Cao, Hongrui; Chen, Xuefeng
Abstract: As a major obstacle to high performance milling, chatter will inevitably decrease tool life, material removal efficiency and workpiece surface quality. Active control based on actuators for chatter suppression has been developed for a long time. However, in traditional active control, the feedback signals are usually time domain vibration signals, which will mitigate both chatter frequencies and normal frequencies, including rotation frequency and its frequency multiplications. In fact, rotation frequency and its frequency multiplications belong to normal cutting phenomenon, which don't need to be suppressed. Therefore, in traditional control strategies, more energy is wasted due to normal frequencies, which cannot obtain the optimal performance and causes the saturation effect of actuators. In order to solve this problem, this paper realized milling chatter suppression based on the adaptive vibration reshaping, which can precisely modify and control the milling vibration frequencies in frequency domain. Hence, the required control forces provided by actuators will decrease a lot, which can optimize the actuator performance and alleviate the saturation effect. Simulation results show that the adaptive vibration reshaping can suppress chatter frequencies effectively without changing rotation frequency and its frequency multiplications, which satisfies the initial control requirement for optimization of actuator performance. Besides, the convergence analysis, the noise resistance performance analysis, the control delay analysis and the chatter frequencies identification errors analysis are also presented for better facilitation to milling chatter suppression. Finally, contrastive milling tests are implemented on a three-axis milling machine. Experimental results show the designed control algorithm can decrease chatter frequencies, while having a little influence on normal frequencies.